Vascular and Inflammatory Factors in the Pathophysiology of Blast-Induced Brain Injury - Elder, Gregory A.; Gama Sosa, Miguel A.; De Gasperi, Rita; Stone, James Radford; Dickstein, Dara L.; Haghighi, Fatemeh; Hof, Patrick R.; Ahlers, Stephen T. (Frontiers in Neurology, 2015)
Blast-related traumatic brain injury (TBI) has received much recent attention because of its frequency in the conflicts in Iraq and Afghanistan. This renewed interest has led to a rapid expansion of clinical and animal studies related to blast. In humans, high-level blast exposure is associated with a prominent hemorrhagic component. In animal models, blast exerts a variety of effects on the nervous system including vascular and inflammatory effects that can be seen with even low-level blast exposures which produce minimal or no neuronal pathology. Acutely, blast exposure in animals causes prominent vasospasm and decreased cerebral blood flow along with blood-brain barrier breakdown and increased vascular permeability. Besides direct effects on the CNS, evidence supports a role for a thoracically mediated effect of blast whereby pressure waves transmitted through the systemic circulation damage the brain. Chronically, a vascular pathology has been observed that is associated with alterations of the vascular extracellular matrix. Sustained microglial and astroglial reactions occur after blast exposure. Markers of a central and peripheral inflammatory response are found for sustained periods after blast injury and include elevation of inflammatory cytokines and other inflammatory mediators. At low levels of blast exposure, a microvascular pathology has been observed in the presence of an otherwise normal brain parenchyma, suggesting that the vasculature may be selectively vulnerable to blast injury. Chronic immune activation in brain following vascular injury may lead to neurobehavioral changes in the absence of direct neuronal pathology. Strategies aimed at preventing or reversing vascular damage or modulating the immune response may improve the chronic neuropsychiatric symptoms associated with blast-related TBI.